1999
DOI: 10.4269/ajtmh.1999.60.329
|View full text |Cite
|
Sign up to set email alerts
|

An intranasal challenge model for testing Japanese encephalitis vaccines in rhesus monkeys.

Abstract: Abstract. Placebo-controlled field efficacy trials of new Japanese encephalitis (JE) vaccines may be impractical. Therefore, an animal model to evaluate efficacy of candidate JE vaccines is sought. Previous work has shown that exposure of monkeys to JE virus (JEV) via the intranasal route results in encephalitis. Here we report the further development of this model and the availability of titered virus stocks to assess the protective efficacy of JE vaccines. To determine the effective dose of our JE challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…The diversity of natural JE strains was reflected in the neutralizing antibody responses of monkeys immunized with ChimeriVax-JE expressing the E protein of a Chinese (genotype 1) virus; prechallenge neutralizing antibodies to heterologous strains were significantly lower than to the homologous vaccine and were undetectable (titer of Ͻ20) in some cases (Table 4). Postchallenge anamnestic responses to heterologous strains were not measured in this study and will be reported elsewhere; however, it is likely that these responses would be characterized by a marked broadening of the antibody response across all JE strains (7,12,26). Cross-protection between heterologous members of the JE antigenic complex has been repeatedly demonstrated (8).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The diversity of natural JE strains was reflected in the neutralizing antibody responses of monkeys immunized with ChimeriVax-JE expressing the E protein of a Chinese (genotype 1) virus; prechallenge neutralizing antibodies to heterologous strains were significantly lower than to the homologous vaccine and were undetectable (titer of Ͻ20) in some cases (Table 4). Postchallenge anamnestic responses to heterologous strains were not measured in this study and will be reported elsewhere; however, it is likely that these responses would be characterized by a marked broadening of the antibody response across all JE strains (7,12,26). Cross-protection between heterologous members of the JE antigenic complex has been repeatedly demonstrated (8).…”
Section: Discussionmentioning
confidence: 97%
“…challenge is intranasal (i.n.) inoculation of high virus doses, which also causes encephalitis (10,26); the i.n. route presumably leads to direct viral spread to the brain via olfactory neurons and is thus simply a delayed form of i.c.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription and amplification were performed for DENV according to Lanciotti and others 7 and for JEV according to Raengsakulrach and others. 8 Routine DENV and JEV assays were able to detect 10 1 tissue culture infective dose (TCID) 50 /mL and 10 1 plaque-forming units per milliliter of specimen, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…ALVAC constructs encoding foreign proteins have been shown to induce humoral and cellular immune responses against a variety of infectious pathogens. These include rabies virus (19,58), feline immunodeficiency virus (59), human immunodeficiency virus type (HIV-1) and HIV-2 (1,4,6,15,18,35,49), Japanese encephalitis virus (32,43), rabbit hemorrhagic disease virus (17), and canine distemper virus (CDV) (39,55), as well as tumor antigens (25,34,46). In fact, very recent studies revealed that mucosal application of ALVAC containing CDV genes induced high titers of neutralizing antibodies (Abs) and protection against a mucosal challenge with CDV (63).…”
mentioning
confidence: 99%